Research Trends on Acrylamide Formation and Mitigation in Coffee Processing over Last Ten Years: A Comprehensive Bibliometric Study - Nazir, N; Syukri, Daimon; Anggraini, Tuty; Fadri, Rince Alfia; Afriliana, Asmak; Kusnadi, Joni; Putri, Annisyia Zarina; Hariry, Amelia; Ito, Nobutaka (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Acrylamide, a potentially carcinogenic compound, forms during high-temperature food processing and has garnered significant attention in the coffee industry due to its implications for public health and food safety. This study analyzes research trends on acrylamide formation and mitigation in coffee processing over the past decade, utilizing bibliometric methods and VOSviewer software. A dataset of publications from 2014 to 2024 was examined to uncover key research themes, leading contributors, and collaborative networks in the field. The analysis reveals a growing body of research focused on understanding the mechanisms of acrylamide formation, developing mitigation strategies, and balancing quality preservation with regulatory compliance. Emerging trends, such as metabolomic approaches and advanced roasting techniques, highlight a shift towards more targeted and sustainable solutions. Additionally, the findings emphasize notable international collaborations, though further interdisciplinary research is needed to address existing gaps and enhance practical applications. This bibliometric study provides valuable insights into the scientific landscape of acrylamide research in coffee processing, offering a foundation for future studies and innovations aimed at ensuring food safety while maintaining coffee quality.